The Influence of Green Human Resources Management (GHRM) on Employee Green Behavior (Green Lifestyle), Employee Performance, and Company Sustainability - Ayu, Mersi Putri; Mellita, Dina; Sartika, Dewi; Trisninawati, Trisninawati (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to assess the effect of Green Human Resource Management (GHRM) on employee green behavior (green lifestyle), employee performance, and corporate sustainability at PT. Northeast Electric Power Construction Project OKI 2. GHRM includes various sustainability-oriented human resource management practices, such as green recruitment, environmental training, environmentally-based performance evaluation, and incentive systems to encourage environmentally friendly behavior in the workplace. This study uses a quantitative approach with a survey method, where data were collected through questionnaires from 70 employees. Data analysis was carried out using statistical techniques such as regression to test the relationship between variables. The results showed that GHRM significantly affects employee green behavior, which in turn contributes to improving employee performance and corporate sustainability. These findings indicate that effective implementation of GHRM can improve the culture of sustainability within an organization, while strengthening the company's competitiveness in the long term. This study contributes to corporate management in developing environmentally-based human resource policies that can improve individual performance and organizational sustainability goals